Electric current–assisted direct joining of silicon carbide. Issue 5 (May 2021) - Li, Huaxin; Koyanagi, Takaaki; Ang, Caen; Katoh, Yutai
Abstract: Conventional direct joining technologies are difficult to use with silicon carbide (SiC) materials, especially for fiber composite forms of SiC, because of the harsh conditions required. To reduce the temperature and/or process time required for the direct joining process, an electric current–assisted joining (ECAJ) method was studied. Joining of low–resistivity grade, nitrogen doped β-SiC was demonstrated at a relatively low nominal temperature of 1750 °C with a 10 min hold by enhancing the passage of current through the material. The joining mechanism is discussed in terms of localized overheating and accelerated self-diffusion at the interface. In the case of joining at 2160 °C for 1 min, rapid crystal growth of textured SiC was found at the interface. This study indicates that rapid ECAJ-based direct joining is a practical and appropriate method for joining SiC-based materials.